Semi-automatic 3D frame modelling of wooden trusses using indoor point clouds. (January 2023) - Otero, Roi; Lagüela, Susana; Cabaleiro, Manuel; Sousa, Helder S.; Arias, Pedro
Abstract: Historical Building Information Modelling (HBIM) is a widely used methodology for the knowledge of the current state of historical buildings, centralizing digital data like geometry, which is the focus of this paper, and more specifically the geometry of the structure of wooden roofs. Their 3D modelling presents some difficulties due to the irregularities in the cross-section of the beams and the complex geometries of the structures, among other reasons. This paper presents a method for the semi-automatic estimation of the framed structure of these 3D structures composed of trusses and beams using as input an indoor point cloud. The methodology consists of the application of two consecutive planar analyses for the location of the beams in the 3D space. The proposed methodology is tested for three different real-world case studies. The framed structure of the three buildings is obtained, serving for the location of the beams in the 3D space and allowing accurate structural analysis. The semi-automatic methodology has shown to be a useful tool for its use in real-world case studies, allowing the performance of structural test, including the estimation of the axial forces diagrams, with the models generated.